1997
DOI: 10.1177/088840649702000405
|View full text |Cite
|
Sign up to set email alerts
|

Teachers Working Together: What Teacher Educators and Researchers Should Know

Abstract: Collaboration among professionals is an essential component of the Individuals with Disabilities Education Act and the cornerstone of successful inclusion efforts. Our review of the literature, however, revealed little research documenting the collaborative efforts of general and special education teachers. We included literature in general and special education to determine the fundamental characteristics of successful collaboration, the barriers to collaboration, and the benefits of collaboration for teacher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 30 publications
0
40
0
4
Order By: Relevance
“…While other studies have not examined the relative effects of the different on-the-job learning opportunities explored here, the notion that collaborative discussion between teachers plays an important role in their development is well supported by previous work suggesting that collaboration improves teachers' knowledge base for teaching (Brownell et al, 1997;Goddard et al, 2007). One additional conceivable explanation for the link between collaborative discussion and teacher change in practice is that when teachers choose to engage with colleagues, they do so around subject matter that is directly relevant to their current teaching practice.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…While other studies have not examined the relative effects of the different on-the-job learning opportunities explored here, the notion that collaborative discussion between teachers plays an important role in their development is well supported by previous work suggesting that collaboration improves teachers' knowledge base for teaching (Brownell et al, 1997;Goddard et al, 2007). One additional conceivable explanation for the link between collaborative discussion and teacher change in practice is that when teachers choose to engage with colleagues, they do so around subject matter that is directly relevant to their current teaching practice.…”
Section: Discussionmentioning
confidence: 52%
“…The extant literature on teacher collaboration indicates that learning is fostered when teachers engage in conversations about new material (Davis, 2003), discuss strategies for effective teaching (Brownell, Yeagar, Rennels, & Riley, 1997;Little, 2003), push one another to experiment around new initiatives (Davis, 2003), work collaboratively to share expertise (Little, 2003;Smylie, 1995), and interpret policy messages (Coburn, 2001). Recent work by Goddard, Goddard, and Tschannen-Moran (2007) suggested that "the more teachers collaborate, the more they are able to converse knowledgably about theories, methods, and processes of teaching and learning, and thus improve their instruction" (p. 879).…”
Section: Empirical and Theoretical Anchorsmentioning
confidence: 99%
“…Specifically, items ask teachers about the frequency with which they have conversations centering on school goals and curriculum, as well as items that ask about the frequency of communication among the whole faculty. Reflective dialogue is theorized to be an integral component of professional learning communities (Kruse, Louis, & Bryk, 1995) and teacher collaboration (Brownell, Yeager, Rennells, & Riley, 1997). This 7-item factor explains 55.3% of the variance (Cronbach's alpha of 0.80).…”
Section: Teachers' Surveysmentioning
confidence: 98%
“…192-193). Teacher collaboration has been proposed as an effective cure for teacher isolation, poor student performance, and lagging professional development (Brownell, Yeager, Rennells, & Riley, 1997;Goddard, Goddard, & Tschannen-Moran, 2007). Teacher collaboration has the potential to increase professional commitment among teachers and positively impact their career satisfaction (Johnson & Birkeland, 2003;Weiss, 1999).…”
Section: Theoretical Frameworkmentioning
confidence: 99%